The discovery of a source of adult hematopoietic cells in the embryo - Dzierzak, Elaine (2008)
This essay is about the 1975 JEEM paper by Françoise Dieterlen-Lièvre (Dieterlen-Lièvre, 1975) and the studies that followed it, which indicated that the adult hematopoietic system in the avian embryo originates, not from the blood islands of the extraembryonic yolk sac as was then believed, but from the body of the embryo itself. Dieterlen-Lièvre’s 1975 paper created a paradigm shift in hematopoietic research, and provided a new and lasting focus on hematopoietic activity within the embryo body.